2021
DOI: 10.2196/33305
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals’ Experiences and Perspectives on Using Telehealth for Home-Based Palliative Care: Protocol for a Scoping Review

Abstract: Background Telehealth seems feasible for use in home-based palliative care. However, acceptance among health care professionals (HCPs) is essential for the successful delivery of telehealth in practice. No scoping review has mapped the experiences and perspectives of HCPs on the use of telehealth for home-based palliative care. Objective The aim of this review is to systematically map published studies on HCPs’ experiences and perspectives on the use of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Finally, our search strategy had language restrictions, as we included only studies in English, Nordic, Spanish, and Portuguese. However, as stated in the published protocol [ 40 ], we were able to include Chinese publications in the initial screening of published studies, although no relevant publications were identified. Due to these limitations, there may be experiences and perspectives from HCPs on the use of telehealth in HBPC we were not able to identify and describe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our search strategy had language restrictions, as we included only studies in English, Nordic, Spanish, and Portuguese. However, as stated in the published protocol [ 40 ], we were able to include Chinese publications in the initial screening of published studies, although no relevant publications were identified. Due to these limitations, there may be experiences and perspectives from HCPs on the use of telehealth in HBPC we were not able to identify and describe.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA-ScR checklist is provided in Multimedia Appendix 1 . Deviations from the published protocol [ 40 ] are shown in Multimedia Appendix 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Most previous initiatives have focused solely on monitoring isolated data, but the HumanITcare platform is comprehensive and consistent. It collects all the data considered especially important for the follow-up of these patients in an intuitive and easy-to-use way for all audiences, thus better controlling each patient’s clinical evolution [ 6 , 7 ]. Until now, data on the correlation between subjective symptom burden and objective parameters have been scarce, so this solution offers an opportunity to collect vital information to fill this gap.…”
Section: Resultsmentioning
confidence: 99%
“…Specific to palliative care, Lundereng et al [ 6 ] point out in their recent review that the potential for telehealth to enhance palliative care has been met with several barriers. In addition to the difficulties described in the general population, there are serious concerns about whether telehealth is acceptable in patients with advanced illnesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation